Erythema elevatum diutinum as the first clinical manifestation of HIV infection: case report - Ana M. Simões; Carlos Monteiro; Isabel Viana (Sociedade Portuguesa de Dermatologia e Venereologia, 2024)
Erythema elevatum diutinum (EED) is a rare form of chronic cutaneous leukocytoclastic vasculitis that is characterized by the appearance of red or purplish papules, plaques, or nodules on the skin. These lesions are typically found on the extensor surfaces of the limbs, such as the elbows, knees, and ankles. EED is frequently associated with other systemic diseases, such as autoimmune diseases, infections, and malignant diseases, particularly hematologic abnormalities. We report a case of EED in a 41-year-old Caucasian male with a previously unknown diagnosis of HIV infection. The treatment was performed with oral dapsone, resulting in complete regression of the lesions after 1 year of treatment.